Proceedings of the 69th Conference and Exhibition - Toms, Julianna; Gurevich, Boris; Muller, Tobias; Johnson, D. (Co-productions, 2007)
Mesoscale heterogeneities occur on a spatial scale, which is greater than pore-scale but less than wavelength scale. The presence of mesoscale heterogeneities in saturating fluids within porous rock causes significant attenuation and phase velocity dispersion. In particular, both contrast in fluid properties and spatial distribution of fluids significantly affects attenuation and dispersion. Thus patchy saturation models need to be flexible in order to account for both contrast and distribution effects. In particular, models which allow arbitrary fluid distributions assume low contrast (or small concentrations) in fluid properties; whilst models which account for fluid contrast assume a fixed periodic distribution of heterogeneities. Here we construct a general model which takes into account both fluid contrast and distribution. We utilize the existing Acoustics of Patchy Saturation (APS) framework of Johnson, which was originally designed for periodically distributed fluid heterogeneities of any contrast. Our approach is to suitably modify specific parameters known as shape and frequency scaling parameters. We do this by analysing and comparing the asymptotic behaviour between different theories to understand how these parameterschange with distribution and contrast. Our new parameters allow modelling of attenuation and dispersion due to arbitrary fluid distributions in 1D and 3D random structures.